Left Ventricular Assist Devices as Bridge to Cardiac Recovery in Nonischemic Heart Failure: Keeping Weaning from the Device in Mind - Akil, Ali; Fischer, Dieter; Holthaus, Alexander J.; Martens, Sven; Scherer, Mirela; Sindermann, Jürgen R. (The Thoracic and Cardiovascular Surgeon, 2016)
A minority of patients on left ventricular assist devices (LVADs) display myocardial recovery raising the question of device explantation. We report a series of seven LVAD patients with nonischemic cardiomyopathy allowing explantation of the VAD. In case of four patients we overview follow-up periods of 4 to 10 years. Remarkably, in three cases device explantation was considered beyond 1 year of LVAD support. Explantation was finally performed after 20 months and more on the device. In light of the scarcity of donor organs we conclude that patients on LVAD support should be evaluated for possible weaning from the device on a regular basis.
Keywords: circulatory assist devices; LVAD; BVAD; cardiomyopathy; heart failure; transplantation; heart